LITERATUR REVIEW: PEMBERIAN BERBAGAI JENIS SEDIAAN DAUN PEPAYA (CARICA PAPAYA L.) UNTUK MENINGKATKAN PRODUKSI ASI PADA IBU MENYUSUI - Desyanti, Harwin Holilah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
One of the breastfeeding problems exclusively is inadequate milk production. Hence, offering papaya leaves is one solution to solve it. Lactogogue contained in papaya leaves can increase the production and secretion of breast milk. Writing this literature review aims to collect and analyze articles about various uses of papaya leaf preparations for breast milk production. The literature search used the Science Direct, Copernicus, SINTA, ResearchGate and Google Scholar databases from 2018 to 2022, then selected according to the topics to be discussed so that 6 articles obtained that matched to the inclusion criteria. The results of the analysis of these 6 articles indicate that offering various kinds of papaya leaf preparations to breastfeeding mothers can increase milk production and secretion